Plant-Soil-Microbiota Combination for the Removal of Total Petroleum Hydrocarbons (TPH): An In-Field Experiment - Zuzolo, Daniela; Guarino, Carmine; Tartaglia, Maria; Sciarrillo, Rosaria (Frontiers in Microbiology, 2021)
The contamination of soil with total petroleum hydrocarbons (TPH) may rise dramatic consequences and need great attention, as soil rehabilitation would need more efforts under a sustainable perspective. However, there is still no known general method since the remediation technology is strictly site-specific. Adaptive biological system dynamics can play a key role to understand and address the potential of situ-specific biological combination for soil pollutants removal. The potential worst-case of TPH contamination reflects soil affected by heavy industrial activities such as oil refinery. Therefore, the experimental trial was conducted on 2,000 m2 area from a contaminated site located in northern Italy. We evaluated the remediation potential over time (270 days) assessing (i) the phytoremediation efficiency of two species of Poaceae (Festuca arundinacea Schreb. and Dactylis glomerata L.) and two species of Fabaceae (Medicago sativa L. and Lotus corniculatus L.), as well as (ii) the role of the indigenous bacteria flora and endo-mycorrhizae consortium addition in plant growth promotion; we also (iii) induced resistance to contamination stress in a field experiment. Thirty-three indigenous bacteria selected from the contaminated soils showed marked plant growth promotion. Moreover, functional metagenomics confirmed the metabolic capability of hydrocarbon degrading microorganisms living in the polluted soil. Our data showed that soil enzymatic activities increased with hydrocarbon degradation rate after 60 days. Both Poaceae and Fabaceae resulted in remarkable remediation potential. Stress marker and antioxidant activity indicated that the selected plant species generally need some time to adapt to TPH stress. In conclusion, our evaluation implied both the rhizosphere effects and functional features of the plant and suggested that plants should (i) have marked tolerance to specific contaminants, (ii) be characterized by an extensive root system and (iii) be susceptible to arbuscular mycorrhizal fungi (AMF) infection.